Analytical study of evacuated annulus tube collector assisted solar desaltification system: A review. (1st September 2020) - Kumar Singh, Ashok; Samsher,
Abstract: Evacuated annulus tube collector (EATC) recommendations in association with solar desaltification systems have a wide scope and lead with remarkable performance to reduce the scarcity of potable water in the subsequent regions among the population, especially in solar rich remote areas. This paper covers the review of the performance of EATC assisted solar desaltification systems with its responsible analytical parameters. An emphasized study on the performance and status of EATC solar desaltification systems has been reviewed thoroughly. Advancements of EATC integrated solar desaltification systems with the effectiveness of EATCs over other collectors have also been discussed. Moreover, thermosiphon EATC solar desaltification systems present a much smarter, self-sustainable, and economic system which does not require any external power to run the system and quite suitable for the remote areas with better self-sustainability rate.